2017
DOI: 10.1016/j.jid.2016.09.030
|View full text |Cite
|
Sign up to set email alerts
|

Deimination of Human Hornerin Enhances its Processing by Calpain-1 and its Cross-Linking by Transglutaminases

Abstract: Hornerin (HRNR) shares numerous features with filaggrin, a key contributor to the epidermal barrier functions. The two proteins display a related structural organization, are expressed by the granular keratinocytes as a large precursor processed by proteolysis, and are cross-linked to the cornified cell envelopes. Two main steps in the metabolism of filaggrin are its deimination and calpain-1 cleavage. Here, using ion-exchange chromatography and two-dimensional gel electrophoresis of human epidermis extracts, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
22
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 15 publications
(26 citation statements)
references
References 30 publications
4
22
0
Order By: Relevance
“…In our western blot analyses combined with 2D electrophoresis, the anti‐CCP antibody was capable of detecting FLG monomer, whereas the anti‐MC antibody likely detected proFLG, its processing intermediates, and the FLG monomer as well as all citrullinated proteins. The more intense FLG immunoreactivity in the 3 epithelial types and additional immunoreactive spots observed by 2D gel electrophoresis indicated the involvement of other citrullinated proteins such as K1, K10 and hornerin …”
Section: Discussionsupporting
confidence: 80%
“…In our western blot analyses combined with 2D electrophoresis, the anti‐CCP antibody was capable of detecting FLG monomer, whereas the anti‐MC antibody likely detected proFLG, its processing intermediates, and the FLG monomer as well as all citrullinated proteins. The more intense FLG immunoreactivity in the 3 epithelial types and additional immunoreactive spots observed by 2D gel electrophoresis indicated the involvement of other citrullinated proteins such as K1, K10 and hornerin …”
Section: Discussionsupporting
confidence: 80%
“…Hornerin is another component of the CE and shares several features with filaggrin including gene localization and organization, as well as protein structure, expression, and function. Overall, HRNR protein, complementary and similar to FLG, plays a role in keratinocyte cornification and contributes to the generation and maintenance of the epidermal barrier . Similar to FLG, HRNR protein is per se expressed in healthy epidermis, increased in skin barrier impaired epidermis, and reduced in the skin of patients with atopic dermatitis (AD) and hand eczema .…”
Section: Introductionmentioning
confidence: 99%
“…Hornerin probably strengthens the envelopes and contributes to their mechanical resistance. We have shown that hornerin is deiminated in vivo; in addition, its deimination improves in vitro its proteolysis by calpain 1 and its cross‐linking by transglutaminases 1 et 3; this suggests that deiminated fragments of hornerin are incorporated into cornified envelopes. In agreement with this hypothesis, cornified envelopes purified from plantar and abdominal human skin do contain deiminated proteins .…”
Section: Normal Function Of Pads In the Epidermal Barriermentioning
confidence: 88%
“…We have shown that hornerin is deiminated in vivo; in addition, its deimination improves in vitro its proteolysis by calpain 1 and its cross‐linking by transglutaminases 1 et 3; this suggests that deiminated fragments of hornerin are incorporated into cornified envelopes. In agreement with this hypothesis, cornified envelopes purified from plantar and abdominal human skin do contain deiminated proteins . Whether additional envelope components including filaggrin and keratins are deiminated and whether addition of deiminated components modifies the envelope properties remain to be demonstrated.…”
Section: Normal Function Of Pads In the Epidermal Barriermentioning
confidence: 88%
See 1 more Smart Citation